MEDIASI KOMITMEN KEBERLANJUTAN DALAM PENGARUH REPUTASI DAN BUDAYA PERUSAHAAN TERHADAP KUALITAS LAPORAN KEBERLANJUTAN - Ardhia, Olivia Maharani; Muawanah, Umi; Farhan, Djuni (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2024)
This study aims to analyze and provide empirical evidence regarding the role of sustainability commitment in mediating the influence of corporate reputation and culture on the quality of sustainability reports. This research is quantitative based, and the data is taken from companies listed on the Indonesia Stock Exchange on the IDX30 index from 2020 to 2023. The sample was determined using purposive sampling, and 54 samples were obtained, which were analyzed using PLS-SEM. The results show that sustainability commitment can fully mediate the relationship between reputation and the quality of sustainability reports. Meanwhile, sustainability commitment partially mediates the relationship between culture and the quality of sustainability reports. These results provide implications that the existence of a sustainability commitment can help a company's reputation support the quality of sustainability reports and encourage a corporate culture that can maximize the quality of sustainability reports.